1981
DOI: 10.1203/00006450-198112000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Adaptation: Sympatho-Adrenal Response to Umbilical Cord Cutting

Abstract: Summaryplasma CAT. In an earlier studv of ~l a s m a CAT in the fetal sheepThe present studies were designed to assess the individual effects of delivery and umbilical cord cutting on the stimulation of the sympatho-adrenal system during parturition. Pregnant ewes with time-dated singleton pregnancies were used in an acutely exteriorized fetal lamb model with an intact umbilical circulation. We observed a minimal, transient elevation in plasma catecholamines (CAT) coincident with the operative procedures and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 13 publications
(19 reference statements)
4
35
0
2
Order By: Relevance
“…Catecholamines do not cross the placenta and in the fetal lamb increase after hypothermia (S), hypoxia (33), hemorrhage (34), labor (32), and umbilical cord cutting (35). The surge in catecholamine that occurs at birth is associated with a rise in plasma FFA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholamines do not cross the placenta and in the fetal lamb increase after hypothermia (S), hypoxia (33), hemorrhage (34), labor (32), and umbilical cord cutting (35). The surge in catecholamine that occurs at birth is associated with a rise in plasma FFA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The surge in catecholamine that occurs at birth is associated with a rise in plasma FFA levels. It has been suggested by Padbury et al (35,36) that this is the primary signal for the initiation of nonshivering thermogenesis. In previous studies (8,23), the initial surge in plasma catecholamines after cooling without ventilation or cord snare was not accompanied by nonshivering thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…I). The order of oxygen ventilation and isoproterenol to simulate the important catecholamine surge at birth (28,37), and volume loading. We measured left ventricular output, vascular pressures, and heart rate, and determined the individual and combined effects of each intervention on these variables.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that oxygen ventilation in utero creates a central circulatory pattern that is identical to the immediate postnatal circulation (3). In addition, the newborn left ventricle functions under significant fJ-adrenergic stimulation (8,37), which is essential to the increase in output at birth (28), and at higher filling pressures (6, 11) than before birth, so we performed the studies during isoproterenol infusion and volume loading in addition to oxygen ventilation. We found that oxygen ventilation and isoproterenol increased left ventricular output, but not volume infusion, and that the effect of oxygen ventilation far exceeded that of isoproterenol.…”
Section: Ascendingaortic Bloodjlow Mean Ascending Aortic Blood Flowmentioning
confidence: 99%
“…It is also interesting to speculate on the mechanisms supporting the LV contraction during the transition from fetal to neonatal circulation. One mechanism can be attributable to the presence of neuroendocrines, especially catecholamines which increase markedly in the circulation at birth (Eliot et al 1980;Padbury et al 1981Padbury et al , 1985, along with the supersensitivity of newborn myocardium to circulating catecholamines (Friedman 1972). In addition, we suggest that the low afterload condition may be one mechanism supporting the LV adaptation to various loading changes shortly after birth.…”
Section: Discussiqnmentioning
confidence: 99%